2007
DOI: 10.1021/ac061387c
|View full text |Cite
|
Sign up to set email alerts
|

Optical Determination of Thallium(I) and Cesium(I) with a Fluorogenic Calix[4]arenebis(crown-6 ether) Containing One Pendent Dansyl Group

Abstract: A fluorogenic derivative of 1,3-alternate calix[4]arenebis(crown-6) (1) containing a dansyl group in the proton-ionizable side arm has been employed in selective sensing of Tl+ and Cs+ at low concentration levels in MeCN-H2O (1:1) mixed solvent. Optical recognition of these two metal cations by 1 occurs in contrasting modes. On the basis of the results of fluorescence, matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS), and 1H NMR studies, Tl+ and Cs+ react with 1 via f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…[21,22] The 1 H and 13 C NMR spectra were also consistent with the expected covalent conjugate and, in particular, the signals of the aromatic carbons of 3 are sensibly deshielded (115-153 ppm), with respect to the dansyl chloride precursor (115-135 ppm), the α methylene protons resonate at δ = 2.84 ppm (Δδ = -0.7 ppm with respect to dansyl-free 2), and the amidic (SO 2 NH) proton resonates at δ = 5.95 ppm, which is a chemical shift close to that obtained for the reference derivative 1 in the same solvent (δ =5.82 ppm). [28] The UV/Vis spectrum of 3 (Ͼ200 nm) displays a shoulder at 218 and a maximum at 250 nm, together with a broad absorbance tail extending up to 450 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,22] The 1 H and 13 C NMR spectra were also consistent with the expected covalent conjugate and, in particular, the signals of the aromatic carbons of 3 are sensibly deshielded (115-153 ppm), with respect to the dansyl chloride precursor (115-135 ppm), the α methylene protons resonate at δ = 2.84 ppm (Δδ = -0.7 ppm with respect to dansyl-free 2), and the amidic (SO 2 NH) proton resonates at δ = 5.95 ppm, which is a chemical shift close to that obtained for the reference derivative 1 in the same solvent (δ =5.82 ppm). [28] The UV/Vis spectrum of 3 (Ͼ200 nm) displays a shoulder at 218 and a maximum at 250 nm, together with a broad absorbance tail extending up to 450 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The dansyl label carries some key optical properties, such as: (i) intense fluorescence in the visible region; (ii) relatively long emission wavelength; (iii) a high Stokes shift behavior preventing self quenching; (iii) solvatochromism, by effect of a twisted intramolecular charge-transfer (TICT) excited state, and (iv) selective excitation/absorption response of the protonated state, leading to antenna-effects in polydansylated arrays. [16,17] These unique features have been successfully exploited for the molecular design of fluorescent chemosensors in which the dansyl chromophore is used in combination with receptor domains, including multi-dentate ligands, [18] supramolecular hosts such as calix [4]arenes, [19] cyclodextrins, [20] crown ethers, [21] and also nano-silica surfaces. [22] Depending on the dansyl environment, selective fluoroionophores have been obtained with interesting sensitivity towards ions such as Pb 2+ , [23] Hg 2+ , [18,24] and Cu 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…At the time of publication, 8 exemplified the first calixarene-based fluorogenic reagent for selective optical sensing of Tl þ . No surprise that under otherwise different conditions of pH, in a contrasting fashion, 8 was found capable of recognising Cs þ as well (58). Favouring of both of these metal ions by the ligand was explained in part by their tendency for cation -p interactions offered by the calix [4]arene framework in 1,3-alternate conformation.…”
Section: Gg Talanova and Vs Talanov 844mentioning
confidence: 96%
“…In particular, it has been reported that spectrofluorimetry using fluorescent probes exhibits many advantages in terms of sensitivity and selectivity in the detection of metal ions such as Cr(VI), 9 Tl(I), and Cs(I). 10 To extend the use of calix [4]arenes as fluorescent probes, we have successfully attached hydroxyquinoline groups to lower rim positions leading to species 1 (5,11,17,23-tetra(tertbutyl)-25,27-bis[(quinoline-8-oxy)propyloxy]-26,28-dihydroxycalix [4]arene) 11,12 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%